Clinical verification of genetic results returned to research participants: findings from a Colon Cancer Family Registry. Issue 6 (23rd August 2017) - Laurino, Mercy Y.; Truitt, Anjali R.; Tenney, Lederle; Fisher, Douglass; Lindor, Noralane M.; Veenstra, David; Jarvik, Gail P.; Newcomb, Polly A.; Fullerton, Stephanie M.
Abstract: Background: The extent to which participants act to clinically verify research results is largely unknown. This study examined whether participants who received Lynch syndrome (LS)‐related findings pursued researchers' recommendation to clinically verify results with testing performed by a CLIA‐certified laboratory. Methods: The Fred Hutchinson Cancer Research Center site of the multinational Colon Cancer Family Registry offered non‐CLIA individual genetic research results to select registry participants (cases and their enrolled relatives) from 2011 to 2013. Participants who elected to receive results were counseled on the importance of verifying results at a CLIA‐certified laboratory. Twenty‐six (76.5%) of the 34 participants who received genetic results completed 2‐ and 12‐month postdisclosure surveys; 42.3% of these (11/26) participated in a semistructured follow‐up interview. Results: Within 12 months of result disclosure, only 4 (15.4%) of 26 participants reported having verified their results in a CLIA‐certified laboratory; of these four cases, all research and clinical results were concordant. Reasons for pursuing clinical verification included acting on the recommendation of the research team and informing future clinical care. Those who did not verify results cited lack of insurance coverage and limited perceived personal benefit of clinical verification as reasons for inaction. Conclusion: These findings suggest researchers will need to address barriers to seeking clinical verification in order to ensure that the intended benefits of returning genetic research results are realized. Abstract : The extent to which participants act to clinically verify research results is largely unknown. This study examined whether participants who received Lynch syndrome‐related findings pursued researchers' recommendation to verify results with testing performed by a CLIA‐certified clinical laboratory. Our study findings suggest researchers will need to address barriers to seeking clinical verification in order to ensure that the intended benefits of returning genetic research results are realized.